The political system and political development in the Sultanate of Oman (Tikrit Journal For Political Science, 2025)
Sultan Qaboos bin Said worked to build a modern state in the Sultanate of Oman by benefiting from oil revenues. He also worked to spread the concepts of political participation, contribution, civil society, and women’s contribution to civil and political life, as well as emphasizing political development. Despite all these matters, Oman has gone through stages of political decline, represented by the popular protests that broke out in 2011, as the Omanis decided to break the barrier of fear and take to the streets, confronting the political system, demanding the advantage of political, social and economic reforms in the structure of the Omani political system, and with regard to the Sultanate’s relationship with neighboring Gulf countries. The Arab, regional and global are in a balanced relationship with each other, and this relationship continued even after the death of Sultan Qaboos and the assumption of power by Sultan Haitham bin Tariq, who made a number of internal political changes in the form of government, ministries, and political and governmental institutions
Keywords: - political system - Sultan Qaboos - political development - Sultanate of Oman